2020
DOI: 10.3390/plants9050643
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Alters Leaf Surface Morphology and Suppresses Insect Herbivory in a Model Grass Species

Abstract: Grasses accumulate large amounts of silicon (Si) which is deposited in trichomes, specialised silica cells and cell walls. This may increase leaf toughness and reduce cell rupture, palatability and digestion. Few studies have measured leaf mechanical traits in response to Si, thus the effect of Si on herbivores can be difficult to disentangle from Si-induced changes in leaf surface morphology. We assessed the effects of Si on Brachypodium distachyon mechanical traits (specific leaf area (SLA), thickness, leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 46 publications
2
41
1
Order By: Relevance
“…The authors also found that the sharp-pointed trichomes present in Nipponbare can puncture holes in the peritrophic membrane of insect midgut, rupturing the gut epithelium, similar to our recent study (Kariyat et al, 2017) on post-ingestive effects of trichomes. Particularly novel, the authors also found that these non-glandular trichomes are further fortified with silica, which has been shown previously to blunt caterpillar mouthparts (Hall, Dagg, Waterman, & Johnson, 2020). Using lsi1 mutants (with non-glandular trichomes but impaired in silica uptake), they found that mutant plants were highly susceptible to damage when compared to O. sativa Oochikara wild type plants, demonstrating the importance of silicification in facilitating plant defense.…”
supporting
confidence: 52%
“…The authors also found that the sharp-pointed trichomes present in Nipponbare can puncture holes in the peritrophic membrane of insect midgut, rupturing the gut epithelium, similar to our recent study (Kariyat et al, 2017) on post-ingestive effects of trichomes. Particularly novel, the authors also found that these non-glandular trichomes are further fortified with silica, which has been shown previously to blunt caterpillar mouthparts (Hall, Dagg, Waterman, & Johnson, 2020). Using lsi1 mutants (with non-glandular trichomes but impaired in silica uptake), they found that mutant plants were highly susceptible to damage when compared to O. sativa Oochikara wild type plants, demonstrating the importance of silicification in facilitating plant defense.…”
supporting
confidence: 52%
“…24 hr after treatment). Although Si can change leaf surface morphology in B. distachyon (Hall, Dagg, et al., 2020), these changes are fairly modest (e.g. larger, but less numerous prickle cells).…”
Section: Discussionmentioning
confidence: 99%
“…Certain plants, particularly in Poaceae, have evolved the ability to actively uptake Si and deposit it in their tissues as silicon dioxide (SiO 2 ), with some plants able to accumulate up to 10% Si dry weight (Hodson et al., 2005; Ma, 2004). The mechanisms by which Si provides a physical defence against biotic stressors (Głazowska et al., 2018; Hall, Dagg, et al., 2020; Massey et al., 2007; Ryalls et al., 2017) and modulates the chemical defence responses to these stressors (Hall et al., 2019; Hall, Mikhael, et al., 2020; Ye et al., 2013) have been the subject of a number of studies over the past two decades (Coskun et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, the exogenous application of methyl jasmonate (which stimulates the JA pathway) to Si supplemented B. distachyon plants resulted in lower JA increases than Si-free plants but still increased foliar Si concentrations in soil [ 35 ] and hydroponic conditions [ 34 ]. Si accumulation typically resulted in changes in leaf surface morphology, such as leaf macro-hairs [ 35 ], silica cells and prickle cells [ 26 ] which have been linked to reduced caterpillar performance [ 26 ]. We did not quantify Si concentrations in the roots, so it is not clear if Si induction arose from increased Si uptake, remobilization of Si from the roots to the leaves or both.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of herbivore defense vary but Si deposition between and within cell walls most likely confers physical resistance to herbivory [ 23 , 24 ]. Moreover, Si may augment leaf trichomes/hairs and form discrete structures (e.g., opaline phytoliths) on the leaf surface [ 25 , 26 ]. These can interfere with feeding, wear down mouthparts and reduce nutrient acquisition by herbivores once ingested [ 27 , 28 ], although these effects vary between plant species [ 29 ].…”
Section: Introductionmentioning
confidence: 99%